A Cross-Country Comparison of National Nutrition Sufficiency Programs in ASEAN Member States: An Integrated Analysis of Strategies, Outcomes, and Best Practices - Putri, Nazwita Dewi (International Health Sciences Journal, 2025)
The Association of Southeast Asian Nations (ASEAN) confronts a persistent "double burden of malnutrition" (DBM), characterized by the coexistence of undernutrition—manifested as stunting and wasting—alongside a rapid increase in overweight, obesity, and diet-related non-communicable diseases (NCDs). This comprehensive analysis integrates systematic literature review findings with strategic archetype analysis to examine national nutrition sufficiency programs across ASEAN member states. Through analysis of 17 studies covering eight ASEAN countries, this study identifies four distinct strategic archetypes based on economic development and nutritional challenges: NCD-Focused High-Income Model (Singapore, Brunei Darussalam), Double-Burden Middle-Income Model (Malaysia, Thailand, Indonesia, Philippines), Undernutrition-Focused Lower-Income Model (Cambodia, Lao PDR, Myanmar, Timor-Leste), and Integrated Success Model (Vietnam). The analysis reveals that political commitment mechanisms fundamentally determine nutrition program success across all ASEAN contexts, operating through resource allocation, multi-sectoral coordination, policy continuity, and implementation barrier resolution. Critical success factors include strong political commitment, effective multi-sectoral coordination, robust surveillance systems, sustainable domestic financing mechanisms, and community-centered implementation strategies. Vietnam emerges as an exemplary model, achieving substantial stunting reductions by embedding nutrition interventions within broader national development frameworks, thereby securing sustainable domestic financing.